A study on consumer awareness of Celcom sukses prepaid towards Indonesian’s migrant in Malaysia / Rani Nerawi - Nerawi, Rani (2009)
This case study exploring the consumer awareness of the product offering by Celcom (Malaysia) Berhad towards Indonesian’s migrant. This newly product is ‘Celcom Sukses’ prepaid. Here, there are some issues in this study that have been analyze the factors that contribute in this issues and discussing some sort of ideas of what Celcom should be taken in order to improve their marketing strategies. In order to justify on what are the organization implement in providing the product and attracting the customer, the observation research has done for 5 months. Through this observation, there are some of issues that related to the consumer awareness which are telecommunication company’s industry, social value, promotion, advertising and competitive environment. On the other words, this study on this issues want to show, what marketing does, in fact, cover a very wide range of absolutely essential business activities that bring to the customer the product that they want, where, when and with all the information that they need to make informed and satisfying customer’s choices. All of these issues deeply explained in the report in order to be more clarifying for understanding of consumer awareness perspectives. On the other hand, it also shows that consumer awareness would also become the priority in achieving the high degree of product performance in the organization. Therefore, there are some of suggestions that have been explained in enhancing the sales target.